Comparison of treatment effects on lateral epicondylitis between acupuncture and extracorporeal shockwave therapy - Clara Wing-Yee Wong; Elaine Yin-Ling Ng; Pui-Wa Fung; Kam-Ming Mok; Patrick Shu-Hang Yung; Kai-Ming Chan (Elsevier, 2017)
Background: Lateral epicondylitis is one of the most common overuse injuries, and has been reported to reduce function and affect daily activities. There is no standard therapy for lateral epicondylitis. In Hong Kong, acupuncture and extracorporeal shockwave therapy (ESWT) have been popular in treating lateral epicondylitis in recent years. Objective: This study is to compare the treatment effects of acupuncture and ESWT on lateral epicondylitis. Methods: In this study, we evaluated 34 patients (34 elbows) with lateral epicondylitis. Seventeen patients were treated by 3-week ESWT, one session per week. Another 17 were treated by 3-week acupuncture therapy, two sessions per week. The outcome measures included pain score by visual analogue scale, maximum grip strength by Jamar dynamometer, and level of functional impairment by disability of arms, shoulders, and hands questionnaire. Participants were assessed at three time points: baseline; after treatment; and 2-week follow-up. Results: The two treatments showed no significant difference at any assessment time-point. Both treatment groups had significant improvement in pain score in longitudinal comparisons. No significant difference was found in maximum grip strength and functional impairment in either treatment group, but a trend of improvement could be observed. In addition, improvement in pain relief stopped when treatment ended for either groups. Conclusions: The treatment effects of acupuncture and ESWT on lateral epicondylitis were similar. The pain relief persisted for at least two weeks after treatment.